Periodontal health awareness among gynecologists in Riyadh, Saudi Arabia - Rahman, Ghousia (J Int Soc Prev Community Dent, 2015)
OBJECTIVE: To determine the knowledge of periodontal disease and pregnancy outcomes among the gynecologists practicing in Riyadh, Saudi Arabia. MATERIALS AND METHODS: A cross-sectional survey of 200 randomly chosen gynecologists from Riyadh was carried out by using a structured, self-administered, closed-ended questionnaire. Knowledge of periodontal disease and possible ways of prevention; knowledge of periodontal disease and pregnancy outcomes; and oral self-care attitudes among gynecologists were assessed. RESULTS: One-quarter of the gynecologists knew the meaning of dental plaque. Almost 57.5% believed that the frequency of toothbrushing should be increased during pregnancy. Eighty percent of gynecologists were aware of the serious effects of smoking on the pregnant woman and her child. Less than half (44.5%) believed that there is a relationship between gum disease and premature labor. Gynecologists working in the government sector were significantly more aware about the causes of inflamed gum in pregnancy, gum disease and its prevention, and negative effects of smoking on pregnancy. A significantly higher percentage of male and senior gynecologists aged between 50 and 54 years answered that gum disease would lead to the delivery of a preterm or low-birth-weight infant. CONCLUSION: Gynecologists considered in the present study showed an acceptable level of knowledge and awareness toward periodontal health and the association between periodontal disease and adverse pregnancy outcomes.